Concerted and birth-and-death evolution of 26S ribosomal DNA in Camellia L. (17th September 2020) - Zhang, Min; Tang, Yi-Wei; Xu, Ying; Yonezawa, Takahiro; Shao, Yang; Wang, Yu-Guo; Song, Zhi-Ping; Yang, Ji; Zhang, Wen-Ju
Abstract: Background and Aims: The ribosomal DNA (rDNA) gene family, encoding ribosomal RNA (rRNA), has long been regarded as an archetypal example illustrating the model of concerted evolution. However, controversy is arising, as rDNA in many eukaryotic species has been proved to be polymorphic. Here, a metagenomic strategy was applied to detect the intragenomic polymorphism as well as the evolutionary patterns of 26S rDNA across the genus Camellia . Methods: Degenerate primer pairs were designed to amplify the 26S rDNA fragments from different Camellia species. The amplicons were then paired-end sequenced on the Illumina MiSeq platform. Key Results: An extremely high level of rDNA polymorphism existed universally in Camellia . However, functional rDNA was still the major component of the family, and was relatively conserved among different Camellia species. Sequence variations mainly came from rRNA pseudogenes and favoured regions that are rich in GC. Specifically, some rRNA pseudogenes have existed in the genome for a long time, and have even experienced several expansion events, which has greatly enriched the abundance of rDNA polymorphism. Conclusions: Camellia represents a group in which rDNA is subjected to a mixture of concerted and birth-and-death evolution. Some rRNA pseudogenes may still have potential functions. Conversely, when released from selection constraint, they can evolve in the direction of decreasing GC content and structural stability through a methylation-induced process, and finally be eliminated from the genome.